No Sinecure Acting as Public Intellectual in Education - Siebren Miedema (Language, Culture, Politics)
The author has earlier made a plea for educators acting as public intellectuals in society to counteract still influential neo-liberal tendencies in educational policies and practices. Against emphases on overstretched attention for measurable output and accountability in education, the aim of education in schools is formulated in terms of holistic personhood formation. Interviewing three educators in different phases of their carrier, it becomes clear that working in academia nowadays it is no sinecure to act as a public intellectual. The author also presents his own experiences in different roles, and makes clear that the instructional niche one is working in could be of utmost importance for really taking that role. To realize a change, it is, according the author, necessary to stop with too much focus on highly cited publications in academic journals, and on individual researchers instead of on research groups working collectively together in joint research programs and with societal partners.